The Origin of Groundwater on the East Slope of Sumbing Vulcano Using Isotopic Methode - Erlinawati, Dina; Putra, Doni Prakasa Eka; Titisari, Anastasia Dewi (2022)
The eastern slope of Sumbing Vulcano, Central Java, Indonesia has many springs that causes most people use springs as a source of raw water. This area is part of the Magelang Temanggung Groundwater Basin which abundant groundwater potential. However water demand will continue to increase along with population growth. Therefore, conservative efforts to protect the recharge area are important. This study aims to determine the characteristics of groundwater recharge area on the eastern slope of Sumbing Vulcano using the isotope method. The research method was carried out by taking rainfall samples at 6 different elevations to obtain the meteoric water line (MWL) and the groundwater samples were taken from 11 stations consist of 10 springs and one deep well. The result shown that the recharge area was coming from local recharge with elevation around 273 masl to 1.208 masl. © Published under licence by IOP Publishing Ltd.